2013
DOI: 10.3390/molecules181215193
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of the Naturally Cytotoxic Triterpenoid Saponin Patrinia-Glycoside B-II and Its Conformer

Abstract: Abstract:The first chemical synthesis of the natural triterpenoid saponin Patrinia-glycoside B-II, namely oleanolic acid]-α-L-arabinopyranoside, has been accomplished in a linear 11-step sequence 11 with 9.4% overall yield. The abnormal 1 C 4 conformation of the arabinose residue was found to occur via conformational fluctuation during preparation of the intermediates. Molecular mechanism and quantum chemistry calculations showed that Patrinia-glycoside B-II and its conformer 1 cannot interconvert under normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
(29 reference statements)
0
10
0
Order By: Relevance
“… NO. Compound Name Molecular Formula Species Reference Triterpenoid aglycones and triterpenoid saponins 1 3- O -β-D-xylopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosyl oleanolic acid C 46 H 74 O 15 PS Li and Lou (2007) 2 Giganteaside D C 41 H 66 O 11 PS Li and Lou (2007) 3 3- O -β-D-glucopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosyl oleanolic acid C 47 H 76 O 16 PS Choi and Woo (1987) 4 Patrinia-glycosides B-II C 47 H 76 O 16 PS Ren et al (2013) 5 Conformer of Patrinia-glycoside B-II C 47 H 76 O 16 PS Ren et al (2013) 6 3- O -β-D-glucopyranosyl-(1 → 3)-α-L-arabinopyranosyl oleanolic acid C 41 H 66 O 12 PS Jiang et al (2003) 7 3- O -α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosyl oleanolic acid C 41 H 66 O 11 PS Nakanishi et al (1993) 8 Oleanolic acid C 30 H ...…”
Section: Phytochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“… NO. Compound Name Molecular Formula Species Reference Triterpenoid aglycones and triterpenoid saponins 1 3- O -β-D-xylopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosyl oleanolic acid C 46 H 74 O 15 PS Li and Lou (2007) 2 Giganteaside D C 41 H 66 O 11 PS Li and Lou (2007) 3 3- O -β-D-glucopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosyl oleanolic acid C 47 H 76 O 16 PS Choi and Woo (1987) 4 Patrinia-glycosides B-II C 47 H 76 O 16 PS Ren et al (2013) 5 Conformer of Patrinia-glycoside B-II C 47 H 76 O 16 PS Ren et al (2013) 6 3- O -β-D-glucopyranosyl-(1 → 3)-α-L-arabinopyranosyl oleanolic acid C 41 H 66 O 12 PS Jiang et al (2003) 7 3- O -α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosyl oleanolic acid C 41 H 66 O 11 PS Nakanishi et al (1993) 8 Oleanolic acid C 30 H ...…”
Section: Phytochemistrymentioning
confidence: 99%
“…); administration 48 h Patrinia-glycosides B-II showed powerful inhibitory activity against eight tumor cell lines at micromolar concentrations (3.4–28.7 μM). PS Ren et al (2013) AGS, SGC-7901, BV-2, 5-FU/HCT-8, HepG2, HT-29, HeLa and MDA-MB-231cells (negative control: culture solution) essential oil extract (The dried whole plant of PS (500 g) was distilled with double distilled water of 5000 mL for 4 h, and the yellow essential oil of 0.2 mg/g (w/w) was obtained. ); 50–200 μg/mL for 24 h The essential oil of PS exhibited remarkable dose-dependent growth inhibition in the dilution range of 50–200 μg/mL.…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports confirmed that a rhamnose unit in the sugar chain attached at C-3 is a structural feature that enhances cytotoxicity of triterpene saponins [ 15 ]. Moreover, a sugar chain that incorporates a monosaccharide unit composed of α- l -rhamnopyranosyl-(1→2)-α- l -arabinopyranosyl located at C-3 is also considered to be a key factor for cytotoxic activity of oleanane type saponins [ 14 , 16 ]. Such a unique disaccharide sequence located at C-3 of serjanic acid may be responsible for the observed activity of compound 1 towards cells grouped in the skin panel (HTB-140, A375, WM793) where the activity of compound 1 was higher as compared to 2 , which is devoid of the terminal rhamnose unit.…”
Section: Resultsmentioning
confidence: 99%
“…These interesting steric behaviors of arabinopyranose cannot be explained by steric hindrance only. In a recent study, there are reports of the inner substituted 1 C 4 conformation of α- l -arabinopyranosyl moiety in triterpene glycoside [14,15]. Many more examples and data need to be collected in future work.…”
Section: Discussionmentioning
confidence: 99%